Digital Disruptions in Education : Students’ Perspective - Gill, Shruti; Sharma, Aarti; Mathur Jain, Daisy (Prabandhan: Indian Journal of Management, 2023)
Purpose : We assessed the students’ anticipations concerning the incorporation of technology in higher education. The study delved into multiple dimensions, encompassing students’ familiarity with educational technologies, the consequences of heightened technology utilization, and strategies for enhancing its efficacy in classroom settings, particularly for cognitive learning. Methodology : Primary deductive research used a survey questionnaire conducted among students from management institutions in Pune and Delhi, with a sample size of 158 respondents. The collected data were analyzed using statistical techniques such as one-sample t-test, paired comparison method, and qualitative analysis with SPSS version 22. The investigation was deductive. Findings : The findings revealed that digital technology enhanced knowledge and learning experiences. However, the research also identified challenges related to technology adoption in educational institutions, primarily due to teachers’ competence and their preference for traditional teaching methods. Practical Implications : This research contributed to understanding how technology tools and facilities could bring about transformative changes and facilitate educators’ and students’ teaching and learning processes. Originality : This study aimed to examine the consequences of digital disruption on traditional educational models and the possible opportunities and problems it brings. This study provided a comprehensive review of the topic while retaining originality in its analysis and insights by examining existing research, scholarly articles, and pertinent sources.